The backyard homestead guide to growing organic food : a crop-by-crop reference for 62 vegetables, fruits, nuts, and herbs - Cobb, Tanya Denckla, 1956- (Backyard homestead., 2024)
"The Backyard Homestead Guide to Growing Organic Food is a one-stop reference for all the key information food gardeners need to grow a healthy, bountiful garden. The book features a comprehensive companion planting guide and an in-depth review of the most effective organic pest control practices, including recipes for how to make your own pest deterrent sprays"--